TELAAH PEMIKIRAN HADIS MAHMUD ABU RAYYAH DALAM BUKU â€œAá¸ŒWAâ€™ â€˜ALA AL-SUNNAH AL-MUHAMMADIYAHâ€ - Sochimin, Sochimin (Hunafa: Jurnal Studia Islamika, 2012)
Abstract: In the development of contemporary hadith studies, especially after the time of Muhammad Abduh, a number of figures who appear to have a critical view of the classical era of hadith studies. Some people rate them as al-Sunnah inkÄr modern. Among the leaders of contemporary famous hadith studies with a view to look a controversial is-Mahmud Abu Rayyah, heavily influenced his thinking and refers to the opinion of Muhammad Abduh and Muhammad Rashid Rida. Critical work of the most popular traditions is the neighbor Adwa '' ala al-Sunnah al-Muhammadiyah. This article will explain in Abu Rayyah critical thinking contained in the book. In preparing Adwa 'ala al-Sunnah al-Muhammadiyah Abu Rayyah much use arguments drawn from modern discipline, consider the hadith contradicts science is á¸aâ€™if.Kata kunci: Abu Rayyah, studi hadis, inkÄr al-sunnah